Functional Diversity Facilitates Stability Under Environmental Changes in an Outdoor Microalgal Cultivation System - Mattsson, Lina; Sörenson, Eva; Capo, Eric; Farnelid, Hanna Maria; Hirwa, Maurice; Olofsson, Martin; Svensson, Fredrik; Lindehoff, Elin; Legrand, Catherine (Frontiers in Bioengineering and Biotechnology, 2021)
Functionally uniform monocultures have remained the paradigm in microalgal cultivation despite the apparent challenges to avoid invasions by other microorganisms. A mixed microbial consortium approach has the potential to optimize and maintain biomass production despite of seasonal changes and to be more resilient towards contaminations. Here we present a three-year outdoor production of mixed consortia of locally adapted microalgae and bacteria in cold temperate latitude. Microalgal consortia were cultivated in flat panel photobioreactors using brackish Baltic Sea water and CO2 from a cement factory (Degerhamn, Cementa AB, Heidelberg Cement Group) as a sustainable CO2 source. To evaluate the ability of the microbial consortia to maintain stable biomass production while exposed to seasonal changes in both light and temperature, we tracked changes in the microbial community using molecular methods (16S and 18S rDNA amplicon sequencing) and monitored the biomass production and quality (lipid, protein and carbohydrate content) over three years. Despite changes in environmental conditions, the mixed consortia maintained stable biomass production by alternating between two different predominant green microalgae (Monoraphidium and Mychonastes) with complementary tolerance to temperature. The bacterial population was few taxa co-occured over time and the composition did not have any connection to the shifts in microalgal taxa. We propose that a locally adapted and mixed microalgal consortia, with complementary traits, can be useful for optimizing yield of commercial scale microalgal cultivation.